International Diversification and Corporate Social Performance: The Subsidiary Activities Impact - Williamson, Peter James; Symeou, Pavlos C.; Zyglidopoulos, Stelios C. (My University, 2018)
We investigate the role that the types of value chain activities undertaken by overseas subsidiaries play in shaping the positive relationship between the firm’s international diversification and Corporate Social Performance (CSP), found in earlier studies. We argue that firms that diversify internationally engage in varying levels of CSP proportionate to the risk of suffering damages to their global legitimacy or reputation from negative events derived from the kinds of activities they engage in through their subsidiaries. Additionally, we posit that the breadth and the depth that a MNC’s international diversification involves interact to magnify the pressures it faces to improve its global CSP. Our results within the context of Extractive Industry Multinationals (EIMs) support all our hypotheses for both social and environmental aspects of CSP.
Keywords: Value chain activities; Overseas subsidiaries; Corporate Social Performance